Chronotype differences in circadian rhythms of temperature, melatonin, and sleepiness as measured in a modified constant routine protocol - Leon Lack (Dove Medical Press, 2009)
Leon Lack, Michelle Bailey, Nicole Lovato, Helen WrightSchool of Psychology, Flinders University, Adelaide, South Australia, AustraliaAbstract: Evening chronotypes typically have sleep patterns timed 2–3 hours later than morning chronotypes. Ambulatory studies have suggested that differences in the timing of underlying circadian rhythms as a cause of the sleep period differences. However, differences in endogenous circadian rhythms are best explored in laboratory protocols such as the constant routine. We used a 27-hour modified constant routine to measure the endogenous core temperature and melatonin circadian rhythms as well as subjective and objective sleepiness from hourly 15-minute sleep opportunities. Ten (8f) morning type individuals were compared with 12 (8f) evening types. All were young, healthy, good sleepers. The typical sleep onset, arising times, circadian phase markers for temperature and melatonin and objective sleepiness were all 2–3 hours later for the evening types than morning types. However, consistent with past studies the differences for the subjective sleepiness rhythms were much greater (5–9 hours). Therefore, the present study supports the important role of subjective alertness/sleepiness in determining the sleep period differences between morning and evening types and the possible vulnerability of evening types to delayed sleep phase disorder.Keywords: chronotype, constant routine, circadian rhythms, sleep propensity, subjective sleepiness